VHL-box and SOCS-box domains determine binding specificity for Cul2-Rbx1 and Cul5-Rbx2 modules of ubiquitin ligases - Kamura, Takumi (Cold Spring Harbor Laboratory Press, 2004)
The ECS (Elongin B/C-Cul2/Cul5-SOCS-box protein) complex is a member of a family of ubiquitin ligases that share a Cullin-Rbx module. SOCS-box proteins recruit substrates to the ECS complex and are linked to Cullin-Rbx via Elongin B/C. VHL has been implicated as a SOCS-box protein, but lacks a C-terminal sequence (downstream of the BC box) of the SOCS box. We now show that VHL specifically interacts with endogenous Cul2-Rbx1 in mammalian cells, whereas SOCS-box proteins associate with Cul5-Rbx2. We also identify LRR-1 and FEM1B as proteins that share a region of homology with VHL (the VHL box, including the BC box and downstream residues) and associate with Cul2-Rbx1. ECS complexes can thus be classified into two distinct protein assemblies, that is, those that contain a subunit with a VHL box (composed of the BC box and a downstream Cul2 box) that interacts with Cul2-Rbx1, and those that contain a subunit with a SOCS box (BC box and downstream Cul5 box) that interacts with Cul5-Rbx2. Domain-swapping analyses showed that the specificity of interaction of VHL-box and SOCS-box proteins with Cullin-Rbx modules is determined by the Cul2 and Cul5 boxes, respectively. Finally, RNAi-mediated knockdown of the Cul2-Rbx1 inhibited the VHL-mediated degradation of HIF-2α, whereas knockdown of Cul5-Rbx2 did not affect it. These data suggest that the functions of the Cul2-Rbx1 and Cul5-Rbx2 modules are distinct.